The Influence of Padlets in Learning Writing Skills on Students of Madrasah Tsanawiyah 2 Payakumbuh - Helhadiani Monika (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2022)
This study aims to knowing the influence of padlets in learning arabic writing skills on students of madrasah tsanawiyah 2 Payakumbuh. The research method used is quantitative study approach that is true experiment method, and data are presented in the form of numbers and analyzed by statistical methods, The method of data collection in this study was to use an writing test by using difference analysis. and the research sample consisted of two groups, namely the control group and the experiment group, each consisting of 20 students, all of them is eighth grade students of Madrasah Tsanawiyah 2 Payakumbuh. This study reached the results, padlet had an effect on student’s arabic writing skill. This can be seen from the average value of the hypothesis thes whose result is 0,02 less than the value of sig.0,05 indicates that this padlet has an influence on learning arabic writing skil for eighth grade students of Madrasah Tsanawiyah 2 Payakumbuh